Active Strategies To Encourage Students Of Plastic Arts To Improve The Productive Writing Skill In English - Espol (2018)
The use of english language through time has been expanded throughout the world, it is the universal language of communication in many fields, and it is the bridge of cultural exchange. it is the language by which scientists and updated information is produced and reproduced. therefore it is an important element in the profesional future. it is said that through writing can be expressed our feelings, ideas, emotions and thoughts by using short compositions with simple structure and vocabulary, but it is also true that young people do not like writing in their own language nor other one.